2021
DOI: 10.3390/ijerph18041397
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Activity and Respiratory Diseases in Adolescents: An Age- and Gender-Matched Study

Abstract: The purpose of the present cross-sectional study was to examine the impacts of allergic respiratory diseases on physical activity (PA), sedentary behaviors (SB), and body mass index (BMI) by matching age and gender with those adolescents without allergic respiratory diseases. This present study analyzed data from the 2019 Korea Youth Risk Behavior Web-based Survey (KYRBWS). Among 57,303 Korean adolescents who responded to the survey, the study divided adolescents into three different groups (i.e., general, ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Although anthropometric information such as body weight and BMI were not significantly different between the two groups, average BMI was higher for both boys and girls in the RD group than those in the general group. Our results are consistent with previous studies [ 31 , 45 , 46 ], which serve as an opportunity to empower the results of prior studies. Furthermore, the RD group’s adolescents who showed a high BMI participated in significantly lower MVPA ( p < 0.05) and spent more than 12 h a week sitting down rather than the general group’s adolescents (general: 33.09%; RD: 38.85%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although anthropometric information such as body weight and BMI were not significantly different between the two groups, average BMI was higher for both boys and girls in the RD group than those in the general group. Our results are consistent with previous studies [ 31 , 45 , 46 ], which serve as an opportunity to empower the results of prior studies. Furthermore, the RD group’s adolescents who showed a high BMI participated in significantly lower MVPA ( p < 0.05) and spent more than 12 h a week sitting down rather than the general group’s adolescents (general: 33.09%; RD: 38.85%).…”
Section: Discussionsupporting
confidence: 92%
“…Although there is little doubt that the cause of the increased prevalence of RD is multifactorial (i.e., environment, air pollution, and genetics) [ 26 , 27 ], there is a growing body of literature that implicates lifestyle changes, specifically decreased PA and HRPF, as being a strong contributor to the increase in RD [ 28 , 29 , 30 ]. As an extension of the aforementioned studies, a recent study conducted by Park and colleagues reported that adolescents with RD participate less in PA and maintain SB longer than those who without RD, and they also have a higher BMI than general adolescents [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the significant role of lifestyle factors in modulating inflammatory responses, it is essential to investigate how modifiable risk factors such as unhealthy dietary practices, lack of physical activity, obesity, and chronic stress can exacerbate the progression of AR ( 7 , 8 ). Among these modifiable factors, diet emerges as a significant adjustable element, offering a potential avenue for the prevention and management of AR through lifestyle modifications.…”
Section: Introductionmentioning
confidence: 99%